RISK FACTOR PROFILE OF ISCHEMIC STROKE PATIENTS - Divastuti, Kedyatasya Rae Fahirah; Setyowatie, Sita; Suryantoro, Satriyo Dwi; Ardhi, Mohammad Saiful (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Stroke remains a leading cause of disability and mortality, with ischemic stroke being the most prevalent type. The high incidence of ischemic stroke is associated with various risk factors, both modifiable and non-modifiable. In Indonesia, limited public awarness and data availability contribute to the increasing burden of ischemic stroke. Objective: This study aims to identify the risk factor profile of ischemic stroke patients in the Inpatient Unit of Universitas Airlangga Hospital, Surabaya. Methods: This retrospective descriptive study utilized secondary data from medical records of patients diagnosed with ischemic stroke between January and December 2023. The variables analyzed included age, gender, hypertension, diabetes mellitus, dyslipidemia, and smoking habits. A total sampling method was applied to the medical records of ischemic stroke patients admitted to the Inpatient Unit of Universitas Airlangga Hospital, Surabaya, during the specified period. Results: Based on 412 collected medical records, the results showed that the most prevalent non-modifiable risk factor was male gender (55.1%), followed by age 45–60 years (44.42%). Meanwhile, the most common modifiable risk factor was dyslipidemia (71.04%), followed by hypertension (66.5%), diabetes mellitus (33.33%), and smoking habit (25.97%). Conclusion: Dyslipidemia was the most prevalent risk factor, followed by hypertension, male gender, age 45–60 years, diabetes mellitus, and smoking habit.